The real ABCs : a surgeon's analysis and a father's legacy - Osher, Robert H, 1949- (SLACK Incorporated, 2019)
"We are all capable of significant Achievements, and this book will analyze the key ingredients that are requisite. I apologize for the flourish of trophies and awards that the reader is subjected to in the following chapters. It is not intended to reflect arrogance or braggadocio, but rather the tangible proof that the strategies for Achievement outlined by the author will pave the road to success. The author admits to constant struggle in this ongoing battle. Finding Balance can be challenging for the high achiever. This book reveals a flurry of mistakes, for which I apologize to those who have been hurt by my laser focus on Achievement. Contentment is the most elusive state and the most difficult to understand. Yet, I have made considerable progress with each passing decade, and I hope to share with the reader some of the life lessons that I have learned"--